ARCHITECTURAL BIOPHILIC PRINCIPLE THAT STIMULATES PSYCHOTHERAPY OF NEUROLOGY PATIENTS IN KANO - ABUBAKAR ALKALI, IBRAHIM (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Biophilic design suggests that incorporating natural elements in the design of built environments could make it more restorative. Strong connections have been found by studies on restorative environments and stimulation of health and wellbeing as benefits of Biophilic design. Biophilic design elements that promote health and wellbeing were found not to be universal. Geographical locations, ailments, culture, orientation, among other factors are found to influence the level of impact of the elements. Using mixed method approach this study explored the stimulating effect of Biophilic design elements in three foremost hospitals in Kano; Aminu Kano Teaching Hospital, Murtala Muhammad General Hospital and Abdullahi Wase specialist Hospital. Data was collected through Questionnaire survey (139 respondents) and interview. The data was analysed using Relative Importance Index (RII) and content analysis. The result shows that Landscape and vegetation, Natural ventilation and Natural lighting with relative importance Index of 0.819, 0.812 and 0.745 respectively are the most outstanding elements of Biophilia that are found to stimulate restoration of neurology patients in Kano. Furthermore Natural materials and Natural forms and shapes (with 0.591 and 0.568) respectively are found to be the elements that have less impact in promoting restoration. Therefore achieving effective restorative environment that aids restoration especially to neurology patients requires serious consideration for Landscape and vegetation, Natural ventilation and Natural lighting.